2013
DOI: 10.1515/ip-2013-0010
|View full text |Cite
|
Sign up to set email alerts
|

>‘Challenging’ times or ‘turbulent’ times: A study of the choice of metaphors used to refer to the 2008 economic crisis in Malaysia and Singapore

Abstract: The choice of metaphor used to refer to a particular concept or event can often be linked to the social, economic, political, or even physical environment in which it is used. Commonly used metaphors, for instance, seeing a political campaign in the context of a war, can be extended to a march toward capturing the seat of the government. This dynamic use of metaphors is illustrated aptly in the Asian Economic Crisis from 1997-1999, which was described in Malaysia using metaphors of colonialism, thus reflecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…By their choice of metaphors, journalists and financial elites may inflict their preferred ideological undertone upon the audience. Media metaphors may redirect responsibility from the companies' management to other actors: the economy, the government or the consumer (Awab & Norazit, 2013;Dalalau, 2013;Williams, Davidson, & Yochim, 2011). From the above literature, it can be concluded that throughout financial crises, financial articles and experts use the same themes and metaphors regardless of the ideology, the context, or the purpose of the news reporting.…”
Section: U N C O R R E C T E D P R O O F S © J O H N B E N J a M I N mentioning
confidence: 99%
“…By their choice of metaphors, journalists and financial elites may inflict their preferred ideological undertone upon the audience. Media metaphors may redirect responsibility from the companies' management to other actors: the economy, the government or the consumer (Awab & Norazit, 2013;Dalalau, 2013;Williams, Davidson, & Yochim, 2011). From the above literature, it can be concluded that throughout financial crises, financial articles and experts use the same themes and metaphors regardless of the ideology, the context, or the purpose of the news reporting.…”
Section: U N C O R R E C T E D P R O O F S © J O H N B E N J a M I N mentioning
confidence: 99%